Student Opinions about their Retirement Future - Płonka, Maria (Olsztyn Economic Journal, 2019)
The paper aims to identify respondents’ attitudes to and awareness of the retirement age and social protection, as well as their expectations with regard to educational activities in this area. The research was carried out in 2018, using an anonymous PAPI type interview on a non-random sample of economics students (N = 703 people) who were either full-time or part-time students. The detailed objectives of the analysis were related to the following issues: – elementary knowledge of social insurance (an open question), – attitudes towards future retirement, care for the elderly, and social solidarity (semantic differential technique combined with the Likert scale), – expectations and opinions regarding the attractiveness and importance of social insurance as a subject of education (techniques as above), – the desire to deepen knowledge in this area (a dichotomous question). The conducted research has shown that despite a lack of expressive attitudes towards social and pension insurance, respondents were interested in deepening their knowledge in this area. This implies the need to create teaching programmes that would broaden this knowledge and build a new insurance awareness based not on demanding attitudes but on the conviction that the retirement future is created independently of the existing system and institutions.